How to Read a Poem and Fall in Love with Poetry - Hirsch, Edward; Duke University. Center for Documentary Studies (1999)
According to Hirsch, poetry is not just a part of life - it is life, and expresses like no other art our most sublime emotions. In this book, he shows how to read a poem, covering verse by, among others, Sylvia Plath, Pablo Neruda and Wordsworth.
"A DoubleTakeBook."
Published in association with the Center for Documentary Studies.
Includes bibliographical references and index.
Keywords: Poetics; Poetry -- History and criticism; Poetry -- Explication; Literature